Analyzing the effectiveness of Facebook and Instagram marketing in digital marketing, scope of conversion and its impact in Bangladesh - Real, Faijul Haque (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.